2015
DOI: 10.1097/txd.0000000000000534
|View full text |Cite
|
Sign up to set email alerts
|

HLA Associations and Risk of Posttransplant Lymphoproliferative Disorder in a Danish Population-Based Cohort

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Previous observational reports demonstrated increased risk of PTLD with different HLA alleles. European studies in SOT recipients suggested that HLA-A18, B21, B45 and HLA-DR13 were associated with increased risk of PTLD 18,20 . Two single-center analyses from U.S. centers described increased risk of PTLD with HLA A-26, B8 and B40 group and risk reduction associated with donor HLA-A1, B8 and DR3 19,21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous observational reports demonstrated increased risk of PTLD with different HLA alleles. European studies in SOT recipients suggested that HLA-A18, B21, B45 and HLA-DR13 were associated with increased risk of PTLD 18,20 . Two single-center analyses from U.S. centers described increased risk of PTLD with HLA A-26, B8 and B40 group and risk reduction associated with donor HLA-A1, B8 and DR3 19,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Donor or recipient HLAs could modulate EBV-specific T cell responses and influence PTLD risk. Several contradictory findings have been reported 18,[20][21][22] , however a dedicated analysis of this association in lung transplant recipients has not been published.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…EBVspecific tumour infiltrating lymphocytes (TILs)/T cells have also been shown to mediate tumor killing in vitro as well as disease remission in patients with NPC (He et al, 2012;Li et al, 2015). HLA-B35, along with HLA-B2, -A2 and -A11 have been shown to be associated with a higher risk of developing posttransplant lymphoproliferative disease (PTLD) post solid-organ transplantation (Pourfarziani et al, 2007), while another study in Denmark showed that HLA-B45 and HLA-DR13 pose an increased PTLD risk (Vase et al, 2015). Indeed, a HLAB35restricted epitope from EBV BZLF1 protein was previously shown to elicit strong cytotoxic T-cell responses (Tynan et al, 2005), while circulating IFN-γ+ CD8+ T cells in patients with PTLD were dominantly reactive to a HLA-B35-restricted epitope from EBV Epstein-Barr nuclear antigen 1 (EBNA1) (Jones et al, 2010).…”
Section: Pathogen-driven Inflammation and Neoplasia: Existing Knowledge And New Insights Viral Pathogens And Immuno-oncogenesismentioning
confidence: 99%
“…The associations between certain HLA phenotypes and the development of post-transplant lymphoproliferative disorders (PTLPD) have been reported in many studies. They showed that the role of HLA with tumour antigen presentation could be involved as either a genetic risk factors, prediction, or the disease protection (1,(4)(5)(6)(7) . In this study, the role of HLA-A alleles as predictive tool for development of non-distractive form of PTLPD among Egyptian live-donor kidney transplant recipients was evaluated.…”
Section: Introductionmentioning
confidence: 99%